Identification of Pseudomonas pseudomallei in clinical practice: use of simple screening tests and API 20NE. - Dance, D A (1989)
The API 20NE kit and a simple screening system involving Gram's stain, the oxidase reaction, colistin and gentamicin resistance, and colonial characteristics on a differential agar medium, were used to test 400 strains of Pseudomonas pseudomallei. The API kit identified 390 (97.5%) strains correctly on first testing and all but one of the remainder on second testing. Only one strain was initially misidentified (as Ps cepacia). The screening system was 100% accurate in identifying Ps pseudomallei. In non-endemic areas the API 20NE kit may be used to identify sporadic imported strains of Ps pseudomallei. Such kits may also help to delineate the geographical distribution of melioidosis. In endemic areas the screening tests described offer a cheap, simple, and accurate means of presumptively identifying Ps pseudomallei from clinical specimens.